UKM Go Global : Eksplorasi Motivasi dan Strategi Memasuki Pasar Internasional - Bayu Prabowo Sutjiatmo (Journal on Education, 2020)
SMEs as the backbone of the nation's economy have great opportunities to enter international markets. The government's agenda for SMEs to upgrade from local to international levels shows government support for SMEs to expand the market to the global realm. This research is a descriptive qualitative research that seeks to explore the motivations of SMEs to enter the international market and explain the strategies for internationalizing SMEs. A case study approach is used to describe the experience of entering the international market. The participants in this study are the owners of PT. Puspa Mandiri which is engaged in the wood working industry and UD Sun Teak Garden which produces classic garden products. Interview transcripts were analyzed by breaking them down into several units and describing their relationship to the existing literature. Based on the results of the interviews, the two companies show a high entrepreneurial spirit marked by an international orientation and a strong commitment to grow and develop business overseas. In addition, social capital is the main key to entering the international market strategy, namely by relying on owned business networks such as contractor partners, large companies, transportation service companies and others